2006
DOI: 10.1104/pp.105.074658
|View full text |Cite
|
Sign up to set email alerts
|

Double-Strand Break Repair in Plants Is Developmentally Regulated  

Abstract: In this study, we analyzed double-strand break (DSB) repair in Arabidopsis (Arabidopsis thaliana) at various developmental stages. To analyze DSB repair, we used a homologous recombination (HR) and point mutation reversion assays based on nonfunctional b-glucuronidase reporter genes. Activation of the reporter gene through HR or point mutation reversion resulted in the appearance of blue sectors after histochemical staining. Scoring of these sectors at 3-d intervals from 2 to 31 d post germination (dpg) reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 54 publications
0
47
0
Order By: Relevance
“…We demonstrated that DNA damage and changes in HRF are not directly proportional to the received dose of ionizing radiation (Kovalchuk et al 2000). In the past, we also showed that plants exposed to stress early during development exhibit the highest increase in HRF (Boyko et al 2006b). Similarly to what was observed for changes in somatic HRF, increase in HRF in the progeny of stressed plants also depended on the severity of stress obtained in parental generation.…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…We demonstrated that DNA damage and changes in HRF are not directly proportional to the received dose of ionizing radiation (Kovalchuk et al 2000). In the past, we also showed that plants exposed to stress early during development exhibit the highest increase in HRF (Boyko et al 2006b). Similarly to what was observed for changes in somatic HRF, increase in HRF in the progeny of stressed plants also depended on the severity of stress obtained in parental generation.…”
Section: Introductionmentioning
confidence: 51%
“…However, it should be noted that in the past, we prorated HRF according to the total number of genomes in the plant under analysis, thus calculating recombination rate (RR). We indeed found that in many cases, changes in HRF and RR in stressed plants were different (Boyko et al 2006b). Larger leaves often mean more cells, but this is not always the case.…”
Section: Changes In Somatic Tissuesmentioning
confidence: 63%
See 1 more Smart Citation
“…In rice, several excision repair genes are expressed predominantly in shoot and root meristems but not in mature leaves (Kimura et al, 2004). It is known that homologous recombinations, an error-free repair pathway, take place more frequently at younger stages during plant development in Arabidopsis (Boyko et al, 2006). It is possible that higher plants employ error-free pathways to maintain an intact genome in undifferentiated tissue, whereas mutagenic bypass is utilized in differentiated tissues notwithstanding the risk of alterations to the genetic information.…”
Section: Plant Development and Mutationsmentioning
confidence: 99%
“…Likewise, XRCC4 and Lig4 homologues have been described in plants, and functionally connected to NHEJ (West et al, 2000;Friesner and Britt, 2003;Kimura and Sakaguchi, 2006;Waterworth et al, 2010). In contrast to the error prone NHEJ pathway, HR is a more accurate repair mechanism that uses homologous DNA strands as templates for repair activities (Boyko et al, 2006a;Boyko et al, 2006b;Li and Ma, 2006;Osman et al, 2011). Several alternative pathways may exist that allow HR based repair of DSBs, however, good evidence is provided for at least two alternative pathways in plants.…”
Section: Fig 3 Schematic Model For Base Excision Repair (Ber)mentioning
confidence: 99%